IL-7-Treated Periodontal Ligament Cells Regulate Local Immune Homeostasis by Modulating Treg/Th17 Cell Polarization - Yu, Xin-Yi; Zhang, Zhao-Qiang; Huang, Jia-Chang; Lin, Jia-Yu; Cai, Xue-Pei; Liu, Chu-Feng (Frontiers in Medicine, 2022)
Both interleukin (IL)-7 and human periodontal ligament cells (hPDLCs) have immunomodulatory properties. However, their combined effect on CD4+T cells has never been studied. In this study, we aimed to investigate the effect of conditioned medium of hPDLCs treated with rhIL-7 on the differentiation of CD4+T cells into regulatory T cells/T helper 17 cells (Treg/Th17 cells) and observe the effect of IL-7 on the immunomodulatory properties of PDLCs. After hPDLCs were treated with different concentrations of rhIL-7 for 24 h, the collected supernatants were used to incubate CD4+T cells for 3 days. A gamma-secretase inhibitor (DAPT) was used to suppress the activation of the Notch1 signaling pathway. Cell proliferation, apoptosis, and necrosis were determined using the cell counting kit-8 (CCK-8) and flow cytometry (FCM). The expressions of forkhead box P3 (Foxp3) in CD4+T cells and transforming growth factor (TGF-β) and IL-6 in the supernatants were determined by ELISA. Reverse transcription-quantitative PCR (RT-qPCR), and the Western blot (WB) determined the mRNA levels and protein expression of various target factors. FCM was used to detect the mean fluorescence intensity of PD-L1 in hPDLCs and to analyze the differentiation of Treg/Th17 cells. Our results showed that IL-7 promoted proliferation and inhibited apoptosis in hPDLCs, promoted the expression of TGF-β, PD-L1, Notch1, Jagged1, and Hes1, and inhibited the levels of hypoxia-inducible factor (HIF)-1α and TCF7, whereas the addition of DAPT effectively reversed these effects. Importantly, we found that the conditioned medium of hPDLCs treated with rhIL-7 promoted the polarization of CD4+T cells into Treg cells but had no significant effect on the differentiation of Th17 cells. Our study indicated that treatment of PDLCs with IL-7 can promote the polarization of CD4+T cells into Treg cells by modulating the expression of inflammatory factors and signaling molecules through activating the Notch1 signaling pathway, thus participating in the regulation of immune homeostasis in the periodontal microenvironment.